National and Religious Types of Periphrases - Ahmadova, Umida (FILOLOGIYA UFQLARI JURNALI, 2024)
The article shows that periphrastic units are one of the methodological tools that ensure the diversity and art of speech. Periphrases have a positive connotation in addition to certain concept, which means that they contain pragmasema, and with the help of these units, people's speech etiquette, culture of communication and society serve to make speech beautiful and fluent.